Analysis of consumer product preference and news media based on data mining technology - Wang, Fang; Fan, Zengguang; Qi, Yuhui (Frontiers in Psychology, 2022)
In order not to be eliminated by the market, enterprises must face various consumer preferences, design products that meet consumer preferences, and enhance competitiveness. This paper combines on-the-spot marketing to study the product preferences of consumers and the personality characteristics of media hosts. This paper introduces the data mining technology of news media into the research of consumer's preference for products. Based on the comprehensive use of media mining technology, customer research theory and product background and foundation, the specific process of influencing consumers' product preference is established. It can be seen from the study that the personality of the anchor has a great relationship with the consumption level of consumers and the sales rate of products, with an impact of 78.53%. Through this study, we can see that there is a certain relationship between consumers' product preference and anchoring personality. Studying the basic characteristics of the phenomenon live broadcast commodity marketing model has important theoretical value for analyzing the live broadcast commodity marketing model. It points out the direction for the scientific, healthy and sustainable development of the future live broadcast commodity marketing mode.